ZAP-70 kinase regulates HIV cell-to-cell spread and virological synapse formation - Sol-Foulon, Nathalie (Nature Publishing Group, 2007)
HIV efficiently spreads in lymphocytes, likely through virological synapses (VSs). These cell–cell junctions share some characteristics with immunological synapses, but cellular proteins required for their constitution remain poorly characterized. We have examined here the role of ZAP-70, a key kinase regulating T-cell activation and immunological synapse formation, in HIV replication. In lymphocytes deficient for ZAP-70, or expressing a kinase-dead mutant of the protein, HIV replication was strikingly delayed. We have characterized further this replication defect. ZAP-70 was dispensable for the early steps of viral cycle, from entry to expression of viral proteins. However, in the absence of ZAP-70, intracellular Gag localization was impaired. ZAP-70 was required in infected donor cells for efficient cell-to-cell HIV transmission to recipients and for formation of VSs. These results bring novel insights into the links that exist between T-cell activation and HIV spread, and suggest that HIV usurps components of the immunological synapse machinery to ensure its own spread through cell-to-cell contacts.